Effects of ammonia on the cellular, physiological, biochemical and genetic traits of Indian major carp (Labeo rohita) fry in artisanal Bangladeshi aquaculture - Kabir Zeehad, Md. Shariar; Mridul, Md. Monirul Islam; Chakrobortty, Dipankar; Mahfuj, Sarower; Aziz, Dania; Hurwood, David A.; Rahi, Md. Lifat (John Wiley & Sons, 2024)
The major carp Rohu (Labeo rohita) is a prime freshwater aquaculture species across the Indian subcontinent that faces various production-related issues associated with water quality parameters. The present study examined the effects of three different doses of NH3 (T1 = 1 mg/L, T2 = 2 mg/L and T3 = 3 mg/L) on cellular (gill ultrastructure), physiological (growth and oxygen consumption rate), biochemical (blood cell counts, blood cortisol and glucose levels) and genetic (expression of five genes involved in growth, immunity and metabolism) traits of Rohu. The experimental ammonia dose significantly affected the tested biological parameters (p < 0.05), causing moderate-to-severe gill tissue damage. In general, compared with those in the control group, 16%–25% slower growth, 12%–30% lower survival and 15%–56% higher O2 consumption were observed for the treatment groups. Blood glucose and cortisol levels increased with increasing ammonia levels, but blood cell counts decreased. The five selected candidate genes showed a differential expression pattern in response to the ammonia dose, with higher expression in the control group and lower expression in the treatment groups. The results indicate that different concentrations of ammonia impose stress on different orders of magnitude in the experimental fishes. Therefore, it can be inferred that the presence of ammonia in aquatic/farming environments can adversely affect production performance; the severity of damage during production depends on the concentration of ammonia. Therefore, maintaining no or minimum ammonia levels in farming environments is urgently needed for sustainable aquaculture production of Rohu.